Pencegahan Kriminalitas Berbasis Al-Qur'an: Kajian Tafsir Wahbah az-Zuhaili dan Relevansinya dengan Program Polrestabes Medan - Alwi Fazri Tjg; Sulaiman Muhammad Amir (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This study aims to examine the Qur’anic-based crime prevention concept as interpreted in Tafsir al-Munir by Wahbah az-Zuhaili and to evaluate its relevance to the preventive programs implemented by the Medan Metropolitan Police (Polrestabes Medan). Employing a qualitative-descriptive approach, this research combines library research and field study. The library research utilizes thematic exegesis (tafsir maudhū‘i) of Qur’anic verses addressing justice, social ethics, and the principle of amr ma‘rūf nahy munkar. Meanwhile, the field study was conducted through semi-structured interviews with police officers and religious leaders engaged in crime prevention outreach. Findings reveal that Qur’anic values such as the prohibition of injustice, the protection of life, property, and dignity, and the duty of family moral education are reflected in various programs led by Polrestabes Medan. These include the door-to-door system, community visits, Friday Dialogues, and collaborations with religious institutions such as MUI and Islamic universities. Periodic evaluations indicate the programs’ effectiveness in enhancing public moral awareness and legal consciousness. Despite challenges such as religious diversity and socio-cultural resistance, the integration of religious approaches strengthens community engagement in maintaining social order. This study concludes that the incorporation of Qur’anic interpretations into public security policy contributes significantly to the development of a just, moral, and secure society.